PENGARUH TOTAL ASSETS TURNOVER DAN FINANCIAL LEVERAGE TERHADAP RETURN ON EQUITY PADA PERUSAHAAN PERDAGANGAN YANG LISTING DI BURSA EFEK INDONESIA - Soedjatmiko -; Hilmi Abdullah; Ahmad Rifani (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2017)
Abstract,The purpose of this study was to determine the influence is there between total assets turnover and financial leverage on the return on equity on a trading company listed on the Indonesia Stock Exchange, either simultaneously or partially.Population and sample in this research is a trading company listed on the Indonesia Stock Exchange totaling 21 companies. Sampling method used in this research is purposive sampling. Regression analysis was used to test the effect of total assets turnover and financial leverage on return on equity.The results of the study during the period 2011 to 2015 show that the total assets turnover shows a positive influence on return on equity. While financial leverage does not affect the return on equity, but simultaneously the total asset turnover and financial leverage have an influence on return on equity.